The association between maternal reminiscing and maternal perpetration of neglect - Kuehn, Molly (Child maltreatment, 2020)
The elaborative and sensitive guidance of maternal reminiscing are robust facilitators of children?s cognitive and socioemotional development. Maternal reminiscing has been identified as impaired among maltreating mothers and as a mechanism linking maltreatment with poor developmental outcomes. Few studies, however, have examined associations between maternal reminiscing and the severity of abuse, neglect, and emotional maltreatment perpetrated by mothers. In the current study, 156 maltreated and 80 nonmaltreated preschoolers (3?6-year-olds) and their mothers reminisced about four emotional events. Maternal reminiscing was coded for elaboration and sensitive guidance. Department of Child Service records were coded for the severity of each maltreatment subtype perpetrated by the mother against the child that reminisced in the study (i.e., target child level) and against any children within the family (i.e., family level). Neglect severity at both target and family levels was negatively associated with maternal sensitive guidance during reminiscing. More severe neglect perpetrated at the family level was associated with lower maternal elaboration. Maternal reminiscing was not significantly associated with abuse severity or emotional maltreatment severity at the target and family levels. These results contribute to a nuanced understanding of maternal reminiscing among maltreating families, with implications for maltreated children?s development and relational interventions.